Genocide under the Statute of the ICC (An Attempt to Organise the Interpretative Issues by Methods of Modern Criminal Law Analysis) - Pohl, Łukasz (The ICC at 25: Lessons Learnt, 2025)
The interpretation of the provisions of the Statute of the International Criminal Court (ICC) defining the grounds of criminal responsibility for the crime of genocide is the subject of many interpretative disputes. However, these disputes are premised on certain theoretical assumptions. These assumptions fall into one of two types: those directly reflected in the text of the Statute, and assumptions that affect interpretation because the interpreter is convinced of such a role. Therefore, the accuracy of both types of assumption can be verified. This chapter focuses on assumptions that emerge in the reconstruction of the norms of the Statute that prohibit genocide. This choice is prompted by the fact that the output of the jurisprudence and the literature appears unsatisfactory. In doing so, this chapter shows that:1) For all crimes under ICC jurisdiction, the provision of the Statute containing the norms prohibiting the commission of crimes is Article 25(2).2) Article 6 of the Statute–the provision that defines the term “genocide”– is the provision that makes the content of this norm adequate.3) Article 25(2)contains the following sanctioned norms: first, prohibition of the killing of members of a protected group; second, prohibition of the infliction of grievous bodily or mental harm on members of a protected group; third, prohibition of the creation of living conditions for a protected group calculated to bring about its physical destruction in whole or in part; fourth, prohibition of the use of measures aimed at stopping births within the protected group; and fifth, prohibition of the forced transfer of children of members of the protected group to another group.4) Article 25(3)(a) indicates that the previously distinguished sanctioned norms prohibiting genocide shall also be violated jointly with another person (this framing constructs the formula of co-perpetration).5) The normative status of the crime of genocide committed through another person has the closest connection to the construction of indirect perpetration.6) In case of behaviours typified in Article 25(3)(b)–namely, the commission, incitement, and inducement to commit the crime of genocide–sanctioned norms are separated from norms prohibiting particular varieties of the crime of genocide (typified in Article 6).7) Article 25(3)(c) does not indicate either the conduct to which aiding and abetting would be relativised or the conduct that the instigator would incite.8) The contribution to the crime of genocide appears to be a highly indeterminate form of behaviour. Consequently, it is challenging to consider “the contribution to the crime” as an appropriately defined object of criminal law regulation, underscoring the need to clarify it in the Elements of Crimes.9) It would be better to use the construction of a “broad intention” here, including the formula of dolus eventualis.10) Article 25(3)(f) specifies that an attempt is the taking of action that initiates the commission of a crime. Here, it seems apparent that a narrowapproach to the attempt to commit the crime of genocide is unconvincing. Certainly, many national criminal law systems adopt a different conception, according to which an attempt is behaviour that starts earlier, namely, at the moment when the perpetrator directly aims at performing a prohibited act. This normative analysis reveals several weaknesses in the Statute concerning the definition of the grounds of criminal responsibility for the crime of genocide. The recommended solution is to improve the substantive quality of specific provisions of the Statute by introducing appropriate explanations to the Elements of Crimes.Keywords: genocide, the Statute of the International Criminal Court, the Elements of Crimes, sanctioned norms